2021
DOI: 10.1177/0300060520986675
|View full text |Cite
|
Sign up to set email alerts
|

Refeeding syndrome in a woman with pancreatitis: a case report

Abstract: Refeeding syndrome can occur in malnourished patients with acute pancreatitis who have electrolyte imbalances. Refeeding syndrome is characterized by severe electrolyte imbalances (mainly hypophosphatemia, hypomagnesemia, and hypokalemia), vitamin deficiency (mainly thiamine deficiency), fluid overload, and salt retention resulting in organ dysfunction and cardiac arrhythmias. We herein report a case involving a patient with severe pancreatitis and gallbladder stones who developed refeeding syndrome with shock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Some reports showed that the diagnosis in clinical practice is based in P-levels not in the pre-feeding period but after clinical manifestations of RS occurred. Table 3 summarizes some case reports of hospitalized patients who presented with RF [24][25][26][27][28] . The HP was the criteria used to identify the RS, and the clinical manifestations were the alert to identify the RS through the electrolyte serum levels.…”
Section: Diagnosis For Rsmentioning
confidence: 99%
“…Some reports showed that the diagnosis in clinical practice is based in P-levels not in the pre-feeding period but after clinical manifestations of RS occurred. Table 3 summarizes some case reports of hospitalized patients who presented with RF [24][25][26][27][28] . The HP was the criteria used to identify the RS, and the clinical manifestations were the alert to identify the RS through the electrolyte serum levels.…”
Section: Diagnosis For Rsmentioning
confidence: 99%